The impact of physical exertion on the level of back pain - Kamińska, Natalia; Perkowski, Radosław (Journal of Education, Health and Sport, 2024)
Introduction: Physical activity is an inherent factor in a healthy lifestyle. Regular exercise allows you to maintain fitness with age and allows for proper functioning of everyday life. The aim of the study was to assess the impact of physical effort on the level of back pain. Materials and methods: The study involved 113 people who were assigned to one of two groups using online surveys, taking into account the level of physical activity. The occurrence of pain was assessed on the basis of the author's questionnaire and Oswestry questionnaire. Results: The subjects from group 2 do not undertake regular physical exercise and more often indicated the occurrence of spine pain. Group 1 showed a statistically significant lower risk of pain than group 2. On the basis of the Oswestry questionnaire, group 2 people are significantly more likely to be less able to perform daily activities than group 1 people. Conclusions: In people undertaking regular physical exercise, less reported pain and lower risk of their occurrence compared to group 2. The group of non-training people show less ability to perform daily activities due to pain.